Dr. Lok Huei Yap — Deep Plane Facelift — Kuala Lumpur - Yap, Lok Huei (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Lok Huei Yap, practicing in Kuala Lumpur, Malaysia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003230; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; malaysia; kuala lumpur